Comparison between sustainable tourism models in force in Spain and Costa Rica; Taking as reference the region of Murcia, Cartagena and the South Caribbean region, Gandoca - Cerdas-Monge, Allan Alexander (2020)
Tourism represents great opportunities for tourist trade, allowing to develop the economy of a region in: human, political, environmental factors allow it to develop with great ease. The environments developed by tourism in the city of Cartagena, Spain, can be determined with the analysis of factors that make a region able to empower itself with such an important activity, allowing to focus the comparison with the models of the region of Gandoca, Sixaola. The research is based on a comparative analysis between both regions that shows the great difference between the two regions.